Gold plasmon-induced photocatalytic dehydrogenative coupling of methane to ethane on polar oxide surfaces. Issue 2 (15th January 2018) - Meng, Lingshu; Chen, Zhenye; Ma, Zhiyun; He, Sha; Hou, Yidong; Li, Hao-Hong; Yuan, Rusheng; Huang, Xi-He; Wang, Xuxu; Wang, Xinchen; Long, Jinlin
Abstract : Au-Plasmon-induced resonance energy transfer modulates the charge carrier energetics of ZnO nanosheets to trigger the stoichiometric conversion of methane into ethane and hydrogen. Abstract : This work shows the solar-driven dehydrogenative coupling of methane to ethane at room temperature. A solar-to-C2 H6 energy conversion efficiency of 0.08% was achieved on the polar surface of Au/ZnO porous nanosheets (NSs), where methane C–H bonds are polarized and dissociated by the local electric field normal to the polar {001} plane, and finally converted into ethane and hydrogen through a radical coupling pathway. Mechanistic studies suggest that the Au-plasmon-induced resonance energy transfer modulates charge carrier energetics to trigger the stoichiometric conversion. Hot electrons reduce protons to H2, which is the rate-determining step of methane coupling.